2012
DOI: 10.1007/s00264-012-1497-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pentoxifylline on histopathological changes in steroid-induced osteonecrosis of femoral head: experimental study in chicken

Abstract: Purpose Pentoxifylline (PTX) is a derivative of methylxanthine and is used in peripheral vascular and cerebrovascular diseases for its effect on the regulation of blood circulation. We investigated whether PTX could be beneficial for femoral head osteonecrosis associated with steroid through these effects. Methods Sixty mature Leghorn type chickens were chosen and divided into three groups. The 25 chickens in group A were given a weekly dose of 3 mg/kg/week methylprednisolone acetate intramuscularly. Four chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
0
28
1
Order By: Relevance
“…The present study is based on this type of metabolism. Osteoblasts, common in the growth of bone tissue, gather in the newly formed bone surface, and have an important role in the process of bone tissue development, bone metabolism and bone mass balance maintenance and damage repair (7)(8)(9). Femoral head necrosis is a common intractable clinical orthopedic disease, and previous studies found that it may be closely associated with the dysfunction of osteoblasts and bone marrow stromal cells (10)(11)(12).…”
Section: Discussionmentioning
confidence: 98%
“…The present study is based on this type of metabolism. Osteoblasts, common in the growth of bone tissue, gather in the newly formed bone surface, and have an important role in the process of bone tissue development, bone metabolism and bone mass balance maintenance and damage repair (7)(8)(9). Femoral head necrosis is a common intractable clinical orthopedic disease, and previous studies found that it may be closely associated with the dysfunction of osteoblasts and bone marrow stromal cells (10)(11)(12).…”
Section: Discussionmentioning
confidence: 98%
“…27 Further, it was reported that corticosteroids alone led to the development of ONFH in Leghorn chickens. 28 Histopathological examination of specimens in this model showed that the subchondral bone trabeculae in the femoral head had disappeared. 28 The diminution of the bone trabeculae was similar in appearance to micro-CT images of an osteoporosis animal model, 29 but it was not clear whether it resulted from osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Histopathological examination of specimens in this model showed that the subchondral bone trabeculae in the femoral head had disappeared. 28 The diminution of the bone trabeculae was similar in appearance to micro-CT images of an osteoporosis animal model, 29 but it was not clear whether it resulted from osteonecrosis. In addition, Yamamoto et al 30 reported an osteonecrosis rabbit model in 1997.…”
Section: Discussionmentioning
confidence: 99%
“…2 Clinically, SANFH is characterized by hip discomfort, pain, activity limitation, limp and shortening of lower limbs. 3 Already proposed direct and indirect pathological mechanisms include apoptosis, inhibit formation of osteoblast and their precursors, vascular endothelial dysfunction, enhanced activity of coagulation, enhance production of ROS, inhibition of angiogenesis and increase adipocytes.…”
Section: Introductionmentioning
confidence: 99%